Towards a Radio-Controlled Time Synchronized Wireless Sensor Network - Ikram,W; Stoianov,I; Thornhill,NF (2010)
Wireless sensor networks are deployed to monitor real-world phenomena, and are seeing growing demand in commerce and industry. These networks can benefit from time synchronized clocks on distributed nodes. The precision of time synchronization depends on error elimination or reliable estimation of errors associated with synchronization message delays. This paper examines an approach to time synchronize motes using onboard radio-controlled clocks. The advantage will be the minimisation of non-deterministic sources of errors in time synchronization amongst receivers. This approach of synchronization using out-of-band and dedicated time source is aimed to achieve network-wide, scalable, topology-independent, fast-convergent and less application-dependent solutions.